Environmental gradients and optimal fixation time revealed with DNA metabarcoding of benthic sample fixative - Vargovčík, Ondrej; Čiamporová-Zaťovičová, Zuzana; Beracko, Pavel; Kopáček, Jiří; Macko, Patrik; Tuhrinová, Kornélia; Čiampor, Fedor (Scientific reports, 2024)
Assessments of biodiversity and ecosystem status can benefit from DNA metabarcoding as a means to streamline sample processing and specimen identification. Moreover, processing the fixation medium instead of the precious material introduces straightforward protocols that allow subsequent focus on certain organisms detected among the preserved specimens. In this study, we present a proof of concept via the analysis of freshwater invertebrate samples from the Tatra Mountain lakes (Slovakia). Besides highlighting a match between the lake-specific environmental conditions and the results of our fixative DNA metabarcoding, we observed an option to fine-tune the fixation time: to prefer two weeks over a day or a month. This effect emerged from the presence/absence of individual taxa rather than from coarse per-sample records of taxonomic richness, demonstrating that metabarcoding studies-and efforts to optimize their protocols-can use the robust metrics to explore even subtle trends. We also provide evidence that fixative DNA might better capture large freshwater species than terrestrial or meiofauna.
Keywords: jezera; taxonomické DNA čárové kódování; Ecosystem; DNA; bezobratlí; Animals; DNA Barcoding, Taxonomic; biodiverzita; Lakes; zvířata; Invertebrates; ekosystém; Biodiversity